Service Quality on Consumer Satisfaction and Non-Wage Consumer Loyalty in BPJS Ketenagakerjaan Pekanbaru Panam Branch - Anwar Hidayat; Teddy Chandra; Rizaldi Putra (Journal of Applied Business and Technology, 2022)
This study aims to analyze the effect of service quality on consumer satisfaction and customer loyalty BPJS Ketenagakerjaan Pekanbaru Panam branch. This research is quantitative research by distributing questionnaires to respondents. The population in this study is the BPJS Ketenagakerjaan branch of Pekanbaru Panam Non-Wage Recipients. The number of samples is 153 respondents. The results of this study indicate that service quality has a positive and significant effect on consumer satisfaction, service quality has a negative and significant effect on consumer loyalty, customer satisfaction has a positive and significant effect on consumer loyalty, and service quality has a significant effect on consumer loyalty through customer satisfaction.